1985
DOI: 10.1063/1.335266
|View full text |Cite
|
Sign up to set email alerts
|

A novel x-ray photoelectron spectroscopy study of the Al/SiO2 interface

Abstract: We report on the first nondestructive measurement of the chemical and physical characteristics of the interface between bulk SiO2 and thick aluminum films. Both x-ray photoelectron spectroscopy (XPS) and electrical measurements of unannealed, resistively evaporated Al films on thermal SiO2 indicate an atomically abrupt interface. Post metallization annealing (PMA) at 450 °C induces reduction of the SiO2 by the aluminum, at a rate consistent with the bulk reaction rate. The XPS measurement is performed from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Previous studies have also investigated the reaction of Al with SiO 2 . Aluminum films deposited on thermally grown SiO 2 surfaces have been shown to reduce SiO 2 and yield Al 2 O 3 and Si according to This reaction is thermodynamically favorable with a Gibbs free energy value of Δ G = −68 kcal/mol at 300 °C . There are similarities between the reactions of TMA and Al with SiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have also investigated the reaction of Al with SiO 2 . Aluminum films deposited on thermally grown SiO 2 surfaces have been shown to reduce SiO 2 and yield Al 2 O 3 and Si according to This reaction is thermodynamically favorable with a Gibbs free energy value of Δ G = −68 kcal/mol at 300 °C . There are similarities between the reactions of TMA and Al with SiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In this analysis, as well, the optical properties of Al 2 O 3 were assigned for the dielectric layer. The procedure was guided by the results of a previous study of Al deposition onto SiO 2 /Si substrates, in which the interaction between Al and SiO 2 has been well characterized. , First, using trial d diel , d metal values, the experimental (ψ, Δ) spectra were mathematically inverted to obtain a trial (ε 1 ,ε 2 ) metal . The constraint was applied that (ε 1 ,ε 2 ) metal must be free of Au interband transition artifacts in the 2.5 eV region.…”
Section: Resultsmentioning
confidence: 99%
“…4). Used originally for exposing the undersides of MOS transistors by etching away the underlying substrate silicon (Hecht et al [62]), the applicability of XeF to micromachined sensors and actuators was demonstrated by Hoffman et al [63]. They showed that with a simple bell-jar setup run at 1 torr, XeF could be sublimed from its solid form at room temperature and that this etch has excellent selectivity with respect to CMOS process layers.…”
Section: Vapor-phase Etchingmentioning
confidence: 99%